Environmental Governance: Challenges of Environmentally Friendly Industrial Areas In Dhaka City of Bangladesh - Jianina, Farahdeusi (International Journal Papier Advance and Scientific Review, 2023)
This research employs a comprehensive approach that takes into account stakeholder views, workforce demographics, and quantitative environmental indicators to investigate environmental governance difficulties in Dhaka's eco-friendly industrial zones. Sector-specific dynamics are revealed by the findings, highlighting the necessity of customized interventions. Higher environmental perception ratings are seen in the electronics industry; nevertheless, there are a variety of obstacles to overcome, such as the chemical industry's pressing need to enhance air quality and the electronics industry's difficulty in reducing waste. The demography of the workforce and attitudes toward the environment are correlated, pointing to possible approaches for promoting sustainability. The study's conclusions offer insights into Dhaka's path toward sustainable industrial growth and implications for stakeholders and future research directions.